2020
DOI: 10.1128/jvi.01410-20
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferon Susceptibility Distinguishes SARS-CoV-2 from SARS-CoV

Abstract: SARS-CoV-2, a novel coronavirus (CoV) that causes COVID-19, has recently emerged causing an ongoing outbreak of viral pneumonia around the world. While distinct from SARS-CoV, both group 2B CoVs share similar genome organization, origins to bat CoVs, and an arsenal of immune antagonists. In this report, we evaluate type-I interferon (IFN-I) sensitivity of SARS-CoV-2 relative to the original SARS-CoV. Our results indicate that while SARS-CoV-2 maintains similar viral replication to SARS-CoV, the novel CoV is mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
162
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(185 citation statements)
references
References 63 publications
22
162
0
1
Order By: Relevance
“…6A). This is consistent with recent reports that SARS-CoV-2 is sensitive to type I interferon treatment 11,[25][26][27] .…”
Section: Evaluation Of the Antivirals Using Sars-cov-2-gfp/n Vlp Celsupporting
confidence: 93%
“…6A). This is consistent with recent reports that SARS-CoV-2 is sensitive to type I interferon treatment 11,[25][26][27] .…”
Section: Evaluation Of the Antivirals Using Sars-cov-2-gfp/n Vlp Celsupporting
confidence: 93%
“…Lokugamage et al recently demonstrated that a pretreatment of VERO cells with 1,000 IU/ml of human IFN-α caused a 2-log 10 drop in viral titer at 48 dpi as compared to control untreated cells (47). We found the same result but using 0.14 IU/ml of rbIFN-λ.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies show that type I and type III IFNs are effective in reducing SARS-CoV-2 replication in VERO cells (18,19,47).…”
Section: Discussionmentioning
confidence: 99%
“…Type I interferons (such as IFN-α, IFN-β) have been shown in clinical trials during the SARS epidemic to have the ability to inhibit the replication of SARS-CoV-1 and therefore improve clinical outcomes (Moriguchi and Sato, 2003). A recent study has shown that SARS-CoV-2 was sensitive to type I inhaled interferon pretreatment in vero cells (Lokugamage et al, 2020) and a small pilot non-randomized study on 33 patients with moderate COVID-19 pneumonia showed that the use of inhaled interferon IFN-k combined with trefoil factor 2 (TFF2), a secreted polypeptide resistant to degradation and hydrolysis, protects the gastrointestinal tract from microbial or chemical induced injury, and was associated with clinical and radiological improvement and viral reversion, therefore resulting in shorter length of stay (Fu et al, 2020). A randomized double-blind placebo-controlled trial to determine the safety and efficacy of inhaled IFN-β1a (SNG001for nebulisation) for patients infected with SARS-CoV-2 is ongoing (ClinicalTrials.gov Identifier: NCT04385095).…”
Section: Introductionmentioning
confidence: 99%